Risk factors for rapid progressive neurological deterioration in patients with cervical spondylotic myelopathy - Zhong, Weiyang; Wang, Lin; Huang, Tianji; Luo, Xiaoji (Journal of orthopaedic surgery and research, 2021)
Background The rapid progressive cervical spondylotic myelopathy (rp-CSM) which had a course of CSM less than 1 month and suffered rapidly progressive neurological deterioration had few reports. Therefore, it is important for us to recognize the pathophysiology of CSM especially the rp-CSM. The study aimed to investigate the risk factors for rapidly progressive (rp) neurological deterioration in patients with cervical spondylotic myelopathy (CSM). Methods A total of 159 patients were reviewed and divided into an rp-CSM group and a chronic-CSM (c-CSM) group. Various clinical indexes, including age, sex, Japanese Orthopaedic Association (JOA) score, intramedullary MR T2-hyperintensity, congenital/degenerative spinal stenosis, and local type of ossification of the posterior longitudinal ligament (OPLL), were analyzed, and independent risk factors were investigated. Results Thirty-four of 159 patients (21.4%) were diagnosed with rp-CSM. All patients were followed up for a mean of 68.56 ± 14.00 months in the rp-CSM group and 62.66 ± 19.95 months in the c-CSM group. No significant difference was found in sex, mean age, smoking and drinking status, diabetes mellitus (DM), hypertension, surgery time, blood loss, JOA score, degenerative spinal stenosis, or OPLL (local). Univariate analyses demonstrated that rp-CSM patients tended to have MR T2-hyperintensity, longer hospital stay, shorter waiting time for surgery, more congenital spinal stenosis, and worse neurological function and to prefer more posterior surgeries than c-CSM patients. A multiple logistic regression analysis showed that congenital spinal stenosis and MR T2-hyperintensity were independently related to the presence of rp-CSM. Conclusions MR T2-hyperintensity and congenital spinal stenosis were risk factors for rp-CSM. Although neurological function deteriorates rapidly, early surgical decompression is recommended and can achieve good neurological recovery after surgery, indicating that rp-CSM could be a reversible condition.